MODERN APPROACHES TO STRATEGIC PLANNING IN THE HIGHER EDUCATION SYSTEM OF AZERBAIJAN IN THE CONTEXT OF ENVIRONMENTAL MANAGEMENT AND SUSTAINABLE DEVELOPMENT (AZƏRBAYCANDA İQTİSADİ İSLAHATLARIN HƏYATA KEÇİRİLMƏSİ XÜSUSİYYƏTLƏRİ VƏ PROBLEMLƏRİ, 2026)
The article examines modern approaches to strategic planning in the higher education system of Azerbaijan under the conditions of global environmental challenges, digital transformation of the economy, and the implementation of sustainable development principles. The study aims to identify the key factors influencing the effectiveness of strategic management in educational institutions and to determine promising directions for the development of environmental education. Theoretical foundations of strategic planning and management in higher education institutions are explored, and contemporary models of integrating environmental principles into the educational process and university governance systems are analyzed. Special attention is given to the role of higher education institutions in forming human capital equipped with competencies in sustainable development, environmental safety, and the green economy. The study investigates international experience in the greening of higher education, including the implementation of environmental management systems, the development of interdisciplinary academic programs, and the expansion of cooperation between universities, government institutions, businesses, and civil society organizations. The potential of digital technologies to enhance the quality of education, improve managerial decision-making, and develop an innovative educational environment is also considered. Based on the analysis, key challenges and limitations in the strategic development of environmental education in Azerbaijan are identified. Priority directions for improving strategic planning are proposed, including the integration of sustainable development principles into educational policy, the advancement of digital infrastructure, the strengthening of international cooperation, and the enhancement of specialist training for an environmentally oriented economy. The findings may be used in developing university strategies and improving national education policy.